Preliminary Design of an Outdoor Mathematics Learning Model through Math Trails in the Cultural Tourism Context of Putri Pinang Masak Park Jambi - Ainun Mardia; Zulkardi; Ratu Ilma Indra Putri; Kamid (Kreano, Jurnal Matematika Kreatif-Inovatif, 2025)
In Indonesia, mathematical learning designs that integrate outdoor learning with the context of local tourism are still very limited, despite the authentic opportunities such environments provide for relating mathematics to real life. The objective of this study is to design an outdoor learning-based mathematics learning model using the Indonesian Realistic Mathematics Education (PMRI) approach, in the context of the Putri Pinang Masak Park cultural tourism destination in the city of Jambi. The approach adopted was design research at the preliminary design stage, which encompassed curriculum analysis, exploration of the mathematical context at the location, and development of a math trail blueprint. The results of this study will show that the tourist environment provides a rich context for geometry, measurement, and proportional reasoning, thereby rendering learning more meaningful, mindful, and joyful. This design contributes to the development of contextual pedagogy and forms the basis for the prototyping and validation stages. Further research is necessary to ascertain the effectiveness of the design in learning practice. Abstrak Desain pembelajaran matematika di Indonesia yang telah mengintegrasikan outdoor learning dengan konteks pariwisata lokal masih sangat minim, sedangkan lingkungan tersebut menyediakan peluang yang autentik untuk mengaitkan matematika dengan kehidupan nyata. Tujuan dari penelitian adalah merancang model pembelajaran matematika berbasis outdoor learning dengan pendekatan Pendidikan Matematika Realistik Indonesia (PMRI), yang dikontekstualisasikan pada destinasi wisata budaya Putri Pinang Masak Park di Kota Jambi. Metode yang digunakan design research pada tahap preliminary design, yang memuat analisis kurikulum, eksplorasi konteks matematis di lokasi, serta pengembangan blueprint math trail. Hasil dari penelitian ini akan menunjukkan bahwa lingkungan wisata menyediakan konteks kaya untuk geometri, pengukuran, serta penalaran proporsional sehingga pembelajaran lebih meaningful, mindful, and joyfull. Desain ini memberikan kontribusi pada pengembangan pedagogi kontekstual dan menjadi dasar bagi tahapan prototyping serta validasi. Penelitian selanjutnya dapat menguji efektivitas desain dalam praktik pembelajaran.